Condition monitoring of variable speed worm gearbox lubricated with contaminated gear oil - Ismon, Maznan (2013)
This research focuses on the condition monitoring of worm gearbox lubricated with contaminated gear oil. The main objectives are to characterize vibration behavior of worm gear as function contaminated lubricant viscosity. Worm gearbox consists of a spirally grooved screw moving against a toothed wheel. Experimental test rig with inverter, electric motor and gearbox to be develop and employed for the investigation. New gear oil with ISO VG 100, 460 and 680 had been indentified to serve the sliding friction of both gears as a comparison to contaminated oil. A predetermine speed of electric motor to be introduced to the gearbox and a set of vibration instrumentations was installed as to capture the vibration signal generated. As to enhance the effectiveness of condition monitoring techniques, temperature rising in the gear oil upon the testing period are monitored using PicoLog Data Logger and later to be analyze. The experiment had revealed that oil with higher viscoscity will contribute to less vibration spectrum. At 900 RPM, the vibration had reduced for about 0.0438 mm/s for ISO VG 100 during the experimental testing within new and contaminated gear oil. It has contribute a reduction of vibration about 51.02% while the temperature monitoring had shown on the higher side compare to the new oil with less viscoscity.